"Concealed cardiomyopathy" as a cause of previously unexplained sudden cardiac arrest. (1st February 2021) - Isbister, Julia C.; Nowak, Natalie; Butters, Alexandra; Yeates, Laura; Gray, Belinda; Sy, Raymond W.; Ingles, Jodie; Bagnall, Richard D.; Semsarian, Christopher
Abstract: Background: Genetic heart disease is a common cause of sudden cardiac arrest (SCA) in the young and those without an ischaemic precipitant. Identifying a cause of SCA in these patients allows for targeted care and family screening. Current guidelines recommend limited, phenotype-guided genetic testing in SCA survivors where a specific genetic condition is suspected and genetic testing is not recommended in clinically-idiopathic SCA survivors. Objective: To investigate the diagnostic utility of broad, multi-phenotype genetic testing in clinically-idiopathic SCA survivors. Methods: Clinically-idiopathic SCA survivors underwent analysis of genes known to be associated with either cardiomyopathy or primary arrhythmia syndromes, following referral to a specialised genetic heart disease clinic in Sydney, Australia between 1997 and 2019. Comprehensive review of clinical records, investigations and re-appraisal of genetic data according to current variant classification criteria was performed. Results: In total, 22% ( n  = 8/36) of clinically-idiopathic SCA survivors (mean age 36.9 ± 16.9 years, 61% male) had a disease-causing variant identified on broad genetic testing. Of these, 7 (88%) variants resided in cardiomyopathy-associated genes ( ACTN2, DES, DSP, MYBPC3, MYH7, PKP2 ) despite structurally normal hearts or sub-diagnostic structural changes at the time of arrest, so-called "concealed cardiomyopathy". Only one SCA survivor had a variant identified in a channelopathy associated gene ( SCN5A ). Conclusion: Extended molecular analysis with multi-phenotype genetic testing can identify a "concealed cardiomyopathy", and increase the diagnosis rate for clinically-idiopathic SCA survivors. Highlights: Current guidelines do not recommend genetic testing in clinically-idiopathic sudden cardiac arrest (SCA) survivors. 22% of clinically-idiopathic SCA survivors carry a disease-causing variant most commonly in cardiomyopathy-associated genes. Multi-phenotype genetic testing can identify "concealed cardiomyopathy", increasing the diagnosis rate for clinically-idiopathic SCA survivors.